Influence of vitamin D-calcium on metabolic profile for gestational diabetes: a meta-analysis of randomized controlled trials - Jin Wang; Qiong Chen; Shaomin Zhang (Taylor & Francis Group, 2024)
Introduction The use of vitamin D-calcium supplementation for treating gestational diabetes remains unclear. This meta-analysis aims to evaluate the efficacy of vitamin D-calcium supplementation in the treatment of gestational diabetes.Methods Several databases including PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases were systemically searched from inception to August 2023, and we included the randomized controlled trials (RCTs) assessing the effect of vitamin D-calcium supplementation on the metabolic profile of gestational diabetes.Results We included five eligible RCTs and 306 pregnant women in this meta-analysis. Compared with control group in pregnant women with gestational diabetes, vitamin D-calcium supplementation was associated with remarkably decreased fasting plasma glucose (SMD=-0.67; 95% CI=-0.93 to −0.41; p <0.00001), serum insulin (SMD=-1.09; 95% CI=-1.89 to −0.29; p = .007) and LDL (SMD=-0.35; 95% CI=-0.63 to −0.06; p = .02), but demonstrated no impact on total cholesterol (SMD=-0.05; 95% CI=-0.81 to 0.71; p = .90) or triglycerides (SMD=-0.14; 95% CI=-0.86 to 0.58; p = .70).Conclusions Vitamin D-calcium supplementation is effective to improve metabolic profile for the treatment of gestational diabetes.